Conservation Status of Marine Biota Sold in Restaurants in Pangandaran Regency, West Java - Permana, Rega; Widayani, Syintyah (Al-Hayat: Journal of Biology and Applied Biology, 2022)
One of most potential activity regarding fisheries business in Pangandaran Regency is seafood restaurants which holds prospect for tourists. However, there are still many restaurants that sell conservationally-important biota. The purpose of this study is to identify the conservation status of marine biota sold in restaurants in Pangandaran Regency. Data was collected by observation or direct survey by purposive sampling in six seafood restaurants. The fish species were then identified for their conservation status based on the International Union for Conservation of Nature (IUCN) and the Convention on International Trade in Endangered Species (CITES). The identification results show that there were biotas included in the IUCN which were Lanjaman Shark (Carcharhinus sealei) with IUCN Appendix II CITES status, Black Fin Shark (Carcharhinus melanopterus) with IUCN Near Threatened (NT) status and Mobula Stingray (Mobula eregoodootenkee) with Endangered status. The results of this study indicated that conservation efforts need to be strengthened.